2019
DOI: 10.1074/jbc.ra118.004254
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase in prolyl oligopeptidase family: Unique enzyme activation and substrate-screening mechanisms

Abstract: Edited by Wolfgang PetiSerine peptidases of the prolyl oligopeptidase (POP) family are of substantial therapeutic importance because of their involvement in diseases such as diabetes, cancer, neurological diseases, and autoimmune disorders. Proper annotation and knowledge of substrate specificity mechanisms in this family are highly valuable. Although endopeptidase, dipeptidyl peptidase, tripeptidyl peptidase, and acylaminoacyl peptidase activities have been reported previously, here we report the first instan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 48 publications
(54 reference statements)
3
32
0
1
Order By: Relevance
“…The low rate of amino-acid conservation at position IV hints that residue X IV could affect the enzymatic activity, given that its side chain has a suitable conformation that does not interfere with the catalytic triad, with amino acids of variable side-chain lengths occurring at position IV, including glutamine [33] and tryptophan [34]. Indeed, residue X IV is suggested to be involved in the optimal configuration of the catalytic triad [32,35] and the enzymatic activity [36][37][38], to participate in substrate binding [15,30,[38][39][40][41] and to affect the thermostability [35] of ABH fold enzymes. Site-directed mutagenesis of residue X IV in different ABH fold enzymes has confirmed its significance in the enzymatic activity, resulting in a wide range of effects upon its replacement: from decreased [32,[35][36][37] and acute loss [38] of enzymatic activity, to improved activity [36,38,41] and increased thermostability [35].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%
See 1 more Smart Citation
“…The low rate of amino-acid conservation at position IV hints that residue X IV could affect the enzymatic activity, given that its side chain has a suitable conformation that does not interfere with the catalytic triad, with amino acids of variable side-chain lengths occurring at position IV, including glutamine [33] and tryptophan [34]. Indeed, residue X IV is suggested to be involved in the optimal configuration of the catalytic triad [32,35] and the enzymatic activity [36][37][38], to participate in substrate binding [15,30,[38][39][40][41] and to affect the thermostability [35] of ABH fold enzymes. Site-directed mutagenesis of residue X IV in different ABH fold enzymes has confirmed its significance in the enzymatic activity, resulting in a wide range of effects upon its replacement: from decreased [32,[35][36][37] and acute loss [38] of enzymatic activity, to improved activity [36,38,41] and increased thermostability [35].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%
“…The tripeptide residue X IV -residue X IV+1 -residue X IV+2 retains its amino-acid conservation in some ABH fold enzyme families, and thus, it is suggested that it can be used as an additional sequence identifier of different ABH fold enzyme families [32,37]. Residue X IV+2 is also extensively studied for the formation of the hydrophobic substrate pocket [22,25,32,[37][38][39][46][47][48] and its role in the enzymatic function [32,49,50].…”
Section: The Conserved Structural Elements That Line the Catalytic Stmentioning
confidence: 99%
“…Acylpeptide hydrolase (APH; EC 3.4.19.1), also known as acylaminoacyl‐peptidase (AAP), is a serine protease, which, together with prolyl oligopeptidase (POP), dipeptidyl peptidase IV (DPPIV) and oligopeptidase B (OB), belongs to the prolyl oligopeptidase family (clan SC, family S9) [1–3] . APH primarily removes N‐acetylated amino acids residues and thus regulates the cellular level of N‐terminal acetylation of proteins [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Prolyl oligopeptidase is a Ser type protease located in the cytoplasm that is twice the size of conventional proteases like trypsin, pepsin, etc. 31 , 32 . This enzyme acts on peptide hormones and neuropeptides to make them functional.…”
Section: Introductionmentioning
confidence: 99%